2023
DOI: 10.1029/2022jb025214
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Gravity in Dissolving Horizontal Fractures

Abstract: Fractures are ubiquitous in geological systems. As reactive fluid flow through a fracture, dissolution of the fracture walls may occur, thus altering the fracture aperture and increasing permeability. It has been recognized that gravity plays an important role in dissolving vertical fractures due to buoyancy‐driven convection. However, the role of gravity in dissolving horizontal fractures is not well understood. Here, we combine microfluidics/Hele‐Shaw experiments and a numerical method to study how the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…The relation ε f + ε s = 1 is valid in a control volume, where ε s is the volume fraction of the solid space. Subsequently, Hu et al 31 developed the modeling approach by incorporating gravitational effects, which is suitable for modeling dissolution processes involving buoyancy-driven convection. Note that the Darcy scale deals with average behavior, while the pore scale refers to the microscopic scale that finely describes physicochemical processes.…”
Section: Overview Of the Flow-through Dissolution Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The relation ε f + ε s = 1 is valid in a control volume, where ε s is the volume fraction of the solid space. Subsequently, Hu et al 31 developed the modeling approach by incorporating gravitational effects, which is suitable for modeling dissolution processes involving buoyancy-driven convection. Note that the Darcy scale deals with average behavior, while the pore scale refers to the microscopic scale that finely describes physicochemical processes.…”
Section: Overview Of the Flow-through Dissolution Experimentsmentioning
confidence: 99%
“…The Boussinesq approximation assumes that we can ignore the effects of density change on the inertial term (left side of eq 1), the gradient pressure term, and the diffusion-like viscosity and only consider the influence of density variation on the buoyancy force term. 31,33,51,52 Some work has indicated that the Boussinesq approximation is valid when the relative density difference is not larger than 10%. 33,51,52 In this work, the maximum relative density difference between inflowing unsaturated and saturated NaCl solutions is 10%.…”
Section: Overview Of the Flow-through Dissolution Experimentsmentioning
confidence: 99%
See 3 more Smart Citations